2012
DOI: 10.2478/v10184-011-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal and dark septate fungal associations in shallot (Allium cepa L. var. aggregatum) under conventional agriculture

Abstract: -We examined roots of the shallot (Allium cepa L. var. aggregatum), one of the most popular cultivated crops of the family Aliaceae, cultivated under conventional agriculture for arbuscular mycorrhizal fungal (AMF) and dark septate fungal endophyte (DSE) associations. All the plants had dual colonization of both AMF and DSE associations. The intermediate-type AMF morphology in the shallot is the first report of this AMF type for the family Aliaceae. The extents of total AMF and DSE colonization ranged from 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
2
8
0
5
Order By: Relevance
“…Priyadharsini et al (2012) reported that shallot roots in conventional agricultural fields had AMF colonization levels within the range of those reported in other studies for other plants. However, the average AMF colonization (49.12%) here is lower than those reported from onions under conventional cultivation in Fevoland (91%) and Zeeland (72%) in Netherlands (Galvan et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
“…Priyadharsini et al (2012) reported that shallot roots in conventional agricultural fields had AMF colonization levels within the range of those reported in other studies for other plants. However, the average AMF colonization (49.12%) here is lower than those reported from onions under conventional cultivation in Fevoland (91%) and Zeeland (72%) in Netherlands (Galvan et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, only one fungal combination (P. turiciensis and G. rosea) decreased the frequency of DSE sclerotia. The intensity of T. repens root infection by intraradical DSE mycelium was not modified by the presence of AMF, showing that both symbionts coexist in several environments (Priyadharsini et al, 2012;Khodke, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…[ 94 ] П роблемы получения высокого урожая и качества про-дукции луковых культур определяются необходи-мостью использования значительного количества минераль-ных удобрений, пестицидов и гербицидов (Anonymous, 1986;Suhardi, 1996). Широкое использование этих растений в пита-нии человека и при этом интенсивные технологии выращива-ния вызывают серьезную экологическую нагрузку на окру-жающую среду.…”
Section: U L F U R -C O N T a I N I N G C O M P O U N D S I N G A R Lunclassified
“…Этот взаимно выгодный симбиоз, называемый микоризой, обеспечивает транспорт энергии и вещества из почвы в растения (Cardon & Whitbeck, 2007), повышает биодоступ-ность нутриентов и воды для растений благодаря глубоко проникающим гифам в поры почвы, недоступные для корне-вых волосков, структурирует ризосферу (Cardon & Whitbeck, 2007). Мицелиальная сеть микоризных грибов часто объеди-няет корневые системы растений на большой площади, защи-щает растения от патогенов и различных биотических и абио-тических стрессов: засухи, засоления, подтопления, воздей-ствия тяжелых металлов и вредных насекомых (Van der Heijden et al, 1998;Smith&Read, 2008;Bolandnazar et al, 2007;Jaime et al, 2008;Gianinazzi et al, 2010).…”
Section: U L F U R -C O N T a I N I N G C O M P O U N D S I N G A R Lunclassified
See 1 more Smart Citation